Pelatihan Teknik Penulisan Karya Ilmiah untuk Siswa MAN 2 Kota Probolinggo - Indro Wicaksono; Hermin Arista; Linda Kurnia; Ari Analisa Rahma (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2021)
The purpose of this training activity is to equip the students of MAN 2 Kota Probolinggo in producing good and interesting scientific work based on students' creative ideas, critical thinking, and innovative. The method of conducting this training includes three stages, the first stage of identifying students who have a desire to write scientific papers and carry out pretests. In the second stage, the delivery of material by means of lecture methods, discussions, and direct practice of the process of preparing scientific work. Next in stage 3, is the student evaluation stage through posttest. The results of this scientific writing technique training include a noticeable improvement in writing techniques, field coverage, and the use of the internet as a reference for scientific work. Increased knowledge of students who are more creative in thinking to find ideas and ideas that can be used as topics to make scientific papers so that it becomes provision for purposes at a higher level.